Assessing implementation challenges in integrated vector borne disease control programs in India using the consolidated framework for implementation research through a systematic review. - Kumar, Vivek; Vyas, Navya; Godinho, Myron Anthony; Raj, S. Elstin Anbu; Govindan, Sreejith (Discover Public Health, 2026)
Background: Vector-borne diseases (VBD) pose significant threats to global public health. Despite the adoption of Integrated Vector Management (IVM) in India to address this issue, its implementation encounters several obstacles that undermine its effectiveness. This review systematically examines implementation challenges and highlights key areas for improving VBD reduction in India. Methods: We conducted a systematic review and meta-synthesis following Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) 2020 guidelines. Studies conducted during 2016–2025 were included in this review, as the first IVM guidelines were introduced in India in 2016. PubMed, Scopus, Embase, and Web of Science databases were included in the search. The Consolidated Framework for Implementation Research (CFIR) was used as a lens to synthesise the evidence. Methodological quality of the included studies was assessed using an appraisal tool based on the study design. Results: Across the 55 studies included, 35 implementation challenges affecting IVM were identified. The most frequently reported barriers included low preventive practices and risk perception (29.1%, n = 16), insecticide resistance (25.5%, n = 14), deficits in community engagement (21.8%, n = 12), and gaps in physical and information technology infrastructure (21.8%, n = 12). System-level challenges related to health workforce capacity, inter-sectoral coordination, financing, and governance were common. Individual-level barriers included knowledge gaps, misconceptions, and limited motivation among communities, as well as training and competency gaps among implementers. Process-related challenges were prominent and included coverage and fidelity gaps, weak engagement, issues with surveillance data quality, and inadequate planning and monitoring. Conclusion: IVM implementation in India reflects interconnected multi-level barriers, particularly within the outer, process and inner domains. Strengthening decentralized, real-time surveillance system with a formal feedback mechanism, alongside institutionalizing community co-design approaches, represents a key approach through theory-informed, context-sensitive implementation strategies to improve implementation fidelity and program effectiveness and accelerate towards Sustainable Development Goal (SDG) 3. Registration: This review protocol was developed and registered in the Open Science Framework (OSF). Registration https://doi.org/10.17605/OSF.IO/JTCWD